Peran Teknologi Finansial dalam Meningkatkan Akses Pembiayaan Usaha Kecil dan Menengah - Aisya, Nafiatul; Atho'illah, Akhmad Yunan (Jurnal Maps (Manajemen Perbankan Syariah), 2025)
The rapid development of financial technology (fintech) has brought about major changes in access to financial services, particularly for micro, small, and medium enterprises (MSMEs) in Indonesia. MSMEs often face obstacles in obtaining formal financing due to limited collateral, low financial literacy, and administrative constraints. The adoption of fintech provides benefits such as easier access to capital, a simpler process without collateral, and smoother cash flow. However, there are also obstacles such as high interest rates, technical system constraints, and limited understanding of fintech products. This study aims to analyze the role of fintech in improving access to financing for MSMEs in Wonocolo, Surabaya, while identifying the challenges faced in adopting these services. The research method used a qualitative approach through interviews with seven MSME actors from various sectors, such as culinary, handicrafts, and printing. The results showed that fintech such as GoPay, OVO, and ShopeePayLater were widely used by MSMEs in Wonocolo for daily transactions and business financing. This utilization provides easy access to unsecured capital, a quick and simple process, and smoothens cash flow, thereby supporting business sustainability. However, a number of obstacles were also found, such as high interest rates, limited digital literacy, and technical disruptions to the application. Thus, although fintech plays a positive role in supporting the efficiency and growth of MSMEs, optimizing its benefits requires improved literacy and adequate regulatory support.